Comparison of different prostatic markers in lymph node and distant metastases of prostate cancer - Queisser, Angela; Hagedorn, Susanne A.; Braun, Martin; Vogel, Wenzel; Duensing, Stefan; Perner, Sven (Modern pathology, 2015)
Prostate cancer is mostly diagnosed at an early stage; however, some tumors are diagnosed in a metastatic stage as cancer of unknown primary origin. In order to allow specific treatment in the case of prostate cancer presenting as cancer of unknown primary origin, it is important to determine the tumor origin. Prostate-specific antigen is used as a diagnostic marker for prostate cancer but the expression declines with progression to castration-resistant prostate cancer. Aim of this study was to identify the most informative marker constellation, which is able to detect metastatic prostate cancer at high sensitivity. The widely used prostate cancer markers such as prostate-specific antigen, prostate-specific acid phosphatase, androgen receptor, prostate-specific membrane antigen, prostein, and ETS-related gene were investigated for their sensitivity to detect prostatic origin of metastases. Expression of prostate-specific antigen, prostate-specific acid phosphatase, androgen receptor, prostate-specific membrane antigen, prostein, and ETS-related gene was determined on archived tissue specimens consisting of benign prostatic tissue (n=9), primary prostate cancer (n=79), lymph node metastases (n=58), and distant metastases (n=39) using immunohistochemistry. The staining intensity was categorized as negative (0), weak (1), moderate (2), and strong (3). All markers except ETS-related gene were able to detect at least 70% of lymph node metastases and distant metastases, with prostate-specific antigen, androgen receptor, and prostate-specific membrane antigen having the highest sensitivity (97%, 91%, and 94%, respectively). A further increase of the sensitivity up to 98% and 100% could be achieved by the combination of prostate-specific antigen, prostate-specific membrane antigen, or androgen receptor for lymph node metastases and for distant metastases, respectively. The same sensitivity could be reached by combining prostate-specific membrane antigen and prostein. Our data show that a combined staining of at least two prostate markers should be utilized to identify metastases as originating from prostate cancer.
Published online 13 June 2014
Gesehen am 16.07.2020